PENGARUH BERMAIN TULISKAN KATAMU TERHADAP MINAT MENULIS ANAK USIA 5-6 TAHUN DI PAUD HARAPAN BANGSA PEKANBARU - Warnawati, Warnawati; Chairilsyah, Daviq; Muktar, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the effect Playing write you say to the interest in writing children aged 5-6 years in PAUD Harapan Bangsa of Pekanbaru . The population and sample of this research is children aged 5-6 years in early childhood Pekanbaru Harapan Bangsa amounted to 14 children. indicators used by Slameto theory (2010 ) of interest . Data collection techniques used are observasi. Technical data analysis used in this study is t test analysis . From the results of the study showed an increase in interest in writing children before and after treatment play write You said amounted to 94.2 % with the r value of 0.822 and a coefficient determinant of ( ) 0.675 which shows that playing Write You said the interest of 67.5 % interest in writing and 32.5 % are influenced by other factors.Keywords : interest in writing , play Write You said